New Palladium(II) Tetraorganodichalcogenoimido Diphosphinates. Crystal and Molecular Structure of Pd[(SPMe2)2N]2 and cis-Pd[(OPPh2)(SPMe2)N]2 - Danut Bilc (Journal of the Mexican Chemical Society, 2000)
Bis(tetraorganodichalcogenoimidodiphosphinato)palladium(II), Pd[(XPR2)(YPR2)N]2, were prepared and investigated bymeans of IR and multinuclear (1H, 13C, 31P) NMR spectroscopy. Thecrystal and molecular structures of Pd[(SPMe2)2N]2 (1) and cis-Pd[(OPPh2)(SPMe2)N]2 (2) were determined by X-ray diffractometry.The crystals of both compounds contain discrete mononuclear molecules.The ligands act as monometallic biconnective units throughboth chalcogen atoms which results in a spiro-bicyclic system withdistorted square planar PdS4 and PdS2O2 core, respectively.